Variation and progression in performance of national junior athletes and their development to national athletes - Clephas, C.; Brückner, J. P. (German Journal of Exercise and Sport Research, 2020)
In high performance sport, it is important to predict future performance in junior athletes. In swimming, different selection criteria have been tested in past research papers. The purpose of this study was to investigate if performance variability could be a selection criterion in junior athletes. We analysed more than 1300 competition results of German national team athletes over seven consecutive years to investigate the development of junior into high performance athletes. We found that variability in general could be a predictor for future success. On average we found a variability overall groups of 1.7% (95% confidence interval 1.6 to 1.8%). Different subgroups varied in the age at which their performance showed least variability. In single age groups we found differences between more successful athletes compared to non-successful athletes. Our investigation suggests that variability could be a promising future performance predictor in junior athletes when subgroup-specific differences are taken into account.